Pemenuhan Hak Narapidana Disabilitas dalam Memenuhi Kesejahteraan Sosial Kelompok Rentan di Lembaga Pemasyarakatan - Misbah Ayu Nafarizka; Mitro Subroto (IAIN Madura, 2021)
In providing protection and guaranteeing the rights of persons with disabilities, the Government makes laws and regulations, namely Law Number 8 of 2016. As a human being, of course, persons with disabilities are not free from mistakes, they can also be subject to imprisonment like other citizens. Prisons as a forum for fostering inmates who have been convicted of committing a crime are not entitled to take away the rights they should have. Inmates only lose their freedom of movement and still get human rights. Prisoners with disabilities have different special needs, where this right must be fulfilled by prisons as stated in Law Number 8 of 2016 concerning Persons with Disabilities. The rights they should get can be in the form of special residential rooms, special toilets for disabilities, special disabled lanes, and wheelchairs/canes to facilitate mobility. In its implementation, there are still some obstacles in fulfilling the rights of prisoners with disabilities, therefore this study uses a normative method aimed at examining library materials and secondary materials such as related laws and regulations. The results of the study indicate that the fulfillment of the rights of prisoners with disabilities in prisons is still not optimal, so there is a need for evaluation and quality improvement carried out by prisons and related institutions, besides that further regulations are needed that focus on guaranteeing the rights of prisoners with disabilities. In its implementation, there are still some obstacles in fulfilling the rights of prisoners with disabilities, therefore this study uses a normative method aimed at examining library materials and secondary materials such as related laws and regulations. The results of the study indicate that the fulfillment of the rights of prisoners with disabilities in prisons is still not optimal, so there is a need for evaluation and quality improvement carried out by prisons and related institutions, besides that further regulations are needed that focus on guaranteeing the rights of prisoners with disabilities. In its implementation, there are still some obstacles in fulfilling the rights of prisoners with disabilities, therefore this study uses a normative method aimed at examining library materials and secondary materials such as related laws and regulations. The results of the study indicate that the fulfillment of the rights of prisoners with disabilities in prisons is still not optimal, so there is a need for evaluation and quality improvement carried out by prisons and related institutions, besides that further regulations are needed that focus on guaranteeing the rights of prisoners with disabilities.